Die Mitte - Mucha, Stanislaw (Germany : Strandfilm Production, 2004)
The stated goal of Polish director Stanistaw Mucha is to ascertain the precise middle point of an ever expanding Europe. Though we do indeed get to see our share of maps and markers, produced by many a concerned EU citizen, Mr. Mucha is not interested in geography so much as a kind of anthropology. His intriguing premise is but an excuse to allow he and his film crew to film a real-life human comedy, gallivanting about Germany and everything East, visiting villages with plaques, countrysides with monuments, and townspeople with legends to sell, all proclaiming that the center lies HERE! The joy to be found here lies in its unique status as a road movie without a narrative trajectory, without an ending or completion. It is a celebration of the myriad faces the camera collects and their hopes, illusions, and good-humored resolve in the face of their sometimes tenuous everyday existence. That this journey takes the film crew as far East as Ukraine should speak volumes of not only the uncertain legacy left by the dissolution of the Soviet Union, but the even more uncertain one beginning in the era of the European Union.
Keywords: Germany